(untitled) (Al-Qamar, 2023)
This article is intended to describe the rules and reasons for the privilege of men’s supervisory role. Islam has established equality between men and women in all matters and has fairly divided the rights and responsibilities so that the institution of the family can run properly. Along with defining the roles of both men and women Islam has imposed the responsibility of supervisory as the caretaker and head of the family on men. So that he supervises all the affairs of the family recognizes their rights and manages to protect them. And maintain family discipline. But unfortunately, it has been considered an injustice to women that men have sovereign rights over women. And thus, he oppresses the woman. A woman can neither raise her voice to protest him nor can she escape him. The concept that is established about the status of men is the result of not understanding Islamic teachings. While man has been declared superior to women by Allah in various respects and the right of leadership in Islam is only granted to him. It is quite a fair decision in the favor of woman. In this article, an attempt has been made to clarify the wisdom of male supervisory and leadership and his superior status in the Islamic family system with a feminist approach.